2022
DOI: 10.3390/cancers14112812
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Confer Gemcitabine Resistance to Pancreatic Cancer Cells through PTEN-Targeting miRNAs in Exosomes

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is currently the third leading cause of cancer-related death in the United States. Even though the poor prognosis of PDAC is often attributed to late diagnosis, patients with an early diagnosis who undergo tumor resection and adjuvant chemotherapy still show tumor recurrence, highlighting a need to develop therapies which can overcome chemoresistance. Chemoresistance has been linked to the high expression of microRNAs (miRs), such as miR-21, within tumor cells. Tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 54 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…RAB27B siRNA Downregulated miR-155 inhibited the release of cancer-derived sEVs and reduced the GEM resistance [142] CAF-derived sEVs GW4869 Suppression of CAF-derived sEV secretion could reduce these PTEN targeting miRNAs and restore the PTEN expression [143] Pan02-derived sEVs Short hairpin RNAs Knocking down of overexpressed genes ITGβ4 or ITGβ5 remarkably reduced the metastatic ability of cancer cells [144] PDAC-derived sEVs (Panc-1, MiaPaCa-2, etc. )…”
Section: Climbazole Imipraminementioning
confidence: 99%
See 1 more Smart Citation
“…RAB27B siRNA Downregulated miR-155 inhibited the release of cancer-derived sEVs and reduced the GEM resistance [142] CAF-derived sEVs GW4869 Suppression of CAF-derived sEV secretion could reduce these PTEN targeting miRNAs and restore the PTEN expression [143] Pan02-derived sEVs Short hairpin RNAs Knocking down of overexpressed genes ITGβ4 or ITGβ5 remarkably reduced the metastatic ability of cancer cells [144] PDAC-derived sEVs (Panc-1, MiaPaCa-2, etc. )…”
Section: Climbazole Imipraminementioning
confidence: 99%
“…[165,166] Katherine et al discovered GEM treated CAFs could release PTEN targeting miR-NAs (miR-21, miR-181a, miR-221, miR-222, and miR-92a) and the suppression of CAF-derived sEV secretion with inhibitor GW4869 could reduce these PTEN targeting miRNAs and restore the PTEN expression. [143] However, these strategies involve the inhibition of sEVs being secreted from both healthy cells and cancer cells. Therefore, their use in cancer treatment should be carefully considered and investigated, as sEVs also play an essential role in regulating normal biological functions as well.…”
Section: Inhibition Of Cancer-derived Sev Formation and Secretionmentioning
confidence: 99%
“…miR-92a-3p could target PTEN expression in PDAC cells. [ 190 ] miR-1290 Prostate cancer Promote EMT and metastasis via targeting GSK3β expression in cancer cell. [ 197 ] miR-146a-5p Prostate cancer Promote cancer metastasis.…”
Section: Cancer-derived Evs Can Dictate Preferable Caf Characteristic...mentioning
confidence: 99%
“…Moreover, a number of studies have found that exosomes participate in the regulation of tumor migration, invasion and angiogenesis, as well as affect various biological processes (e.g., tumor immune escape and chemoresistance) in different types of tumors (e.g., breast 5 , lung 6 , prostate 7 , and colon 8 ). In PC, Richards et al found that exosomes secreted by cancer-associated fibroblasts could regulate cell proliferation and confer resistance to gemcitabine through miRNAs targeting phosphatase and tensin homolog (PTEN) 9 . Additionally, exosomes with downregulated hsa_circ_0000069 could suppress the malignant transformation of human pancreatic duct epithelial cells 10 .…”
Section: Introductionmentioning
confidence: 99%